The Spectrum of Peripheral-Vestibular Deficits and Their Change Over Time in CANVAS/RFC1-Related Ataxia Systematic Review and Meta-Analysis of Quantitative Head-Impulse Testing - Maja Szymanska Heydel; Felix Heindl; Annette Hartmann; Max Borsche; Andreas Traschütz; Dominik Straumann; Michael Strupp; Alexander Andrea Tarnutzer (The Cerebellum, 2025)
Cerebellar ataxia, neuropathy, vestibular-areflexia syndrome (CANVAS) has been linked to biallelic intronic repeat-expansions in RFC1 . Video-head-impulse testing (vHIT) offers a quantitative assessment of the angular vestibulo-ocular reflex (aVOR) of all three canals. We evaluated patterns of peripheral-vestibular impairment, its change over time and evaluated correlations with other parameters. PubMed/Embase were searched for articles reporting vHIT in patients with CANVAS/RFC1-related ataxia. A multiple linear-regression model was used to analyse relationships between vHIT-gains and clinical parameters (age, disease duration, sex, biallelic RFC1 expansion). A special focus was put on sequential vHIT in individual patients. 23/64 studies met inclusion criteria; additional 13 studies were identified through reference screening. Twenty-five studies reported individual vHIT-gains and demographic data, suitable for quantitative analysis. Substantial aVOR-gain reductions were found for horizontal (0.32 ± 0.02, n = 146 patients), anterior (0.39 ± 0.03, n = 27) and posterior (0.29 ± 0.03, n = 27) canals. Linear regression showed an association between horizontal vHIT-gains ( n = 146 patients; range of gain: 0-1.3) and disease duration (range: 0–444 months, coef. =-0.0048, p = 0.031) and male sex (coef. =-0.1604, p < 0.001). A decline in horizontal-canal vHIT-gains at least one side over time was noted in 15/21 patients after a mean follow-up time of 33.4 ± 10.7 months. vHIT is a potential biomarker for monitoring progression of CANVAS/RFC1-related ataxia. The significant association between reduced vHIT-gains and disease duration, and their intra-individual decline over time emphasize that impairment of the aVOR reflects the underlying neurodegenerative disease process. Multi-centre prospective studies are needed for systematic early screening and longitudinal validation as outcome for future targeted therapy trials.